2013
DOI: 10.1080/00224545.2013.768592
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Prejudice: Different Patterns for Two Types of Religious Internalization

Abstract: The literature on the relationship between religiosity and prejudice has shown inconsistent findings. We argue that it is necessary to distinguish between different types of religiosity and that its relationship with prejudice is mediated by different values. Results of two studies conducted in Italy show that identified religiosity and introjected religiosity predict different levels of prejudice toward Muslim immigrants. Moreover, the negative relationship between identified religiosity and prejudice was med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Both of these processes of searching involve youths’ reaching outside of themselves and thinking outside the box, which includes a level of uncertainty that might make religious parents, educators, and leaders somewhat uncomfortable (e.g., the youths could decide to leave the church). Nevertheless, it opens up the possibility for a deeper level of religiosity and spirituality, and greater connection to all of humanity (Brambilla et al, 2013; Lerner et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these processes of searching involve youths’ reaching outside of themselves and thinking outside the box, which includes a level of uncertainty that might make religious parents, educators, and leaders somewhat uncomfortable (e.g., the youths could decide to leave the church). Nevertheless, it opens up the possibility for a deeper level of religiosity and spirituality, and greater connection to all of humanity (Brambilla et al, 2013; Lerner et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, higher religiosity has been associated with increased support for torture as a means of obtaining information from terrorist suspects (Malka & Soto, ). Increased religiosity has also predicted decreased support for immigration of disfavored groups (Brambilla, Manzi, Regalia, & Verkuyten, ), and religiosity covaries along with voting intentions in response to ovulation cycles (Durante, Rae, & Griskevicius, ). As such, there is strong evidence to expect religiosity to be associated with both the endorsement of the binding moral foundations and political outcomes.…”
Section: Demographic Variables Moral Foundations and Politicsmentioning
confidence: 99%
“…In terms of interreligious relations, previous studies reported that religious people can be either more or less tolerant toward outgroup members (Allport, 1958; Brambilla, Manzi, Regalia, & Verkuyten, 2013). Brambilla et al (2013) demonstrated that individuals who identify with a religion that endorses prosocial values were negatively related to prejudice; in contrast, religious people who conform to norms saying that they should distrust those who are from different beliefs were found positively related to prejudice. The findings suggest that it is not their religiosity that makes people tend to be prejudiced or tolerant, but it depends how the religion is internalized; it depends on how it is shown or understood.…”
Section: Religious Groups and Its Members’s Perceptionsmentioning
confidence: 99%